Autonomy - Parchomovsky, Gideon; Stein, Alex (University of Toronto Law Journal, 2021)
Personal autonomy is a constitutive element of all rights. It confers upon a right-holder the power to decide whether, and under what circumstances, to exercise her right. Every right infringement thus invariably involves a violation of its holder’s autonomy. The autonomy violation consists of the deprivation of a right-holder of a choice that was rightfully hers – the choice as to how to go about her life. Harms resulting from the right’s infringement and from the autonomy violation are often readily distinguishable, as is the case when someone uses the property of a right-holder without securing her permission or, worse, causes her bodily injury. At other times, however, the two harms overlap, as in the case when a right-holder is unlawfully barred from exercising her free speech right or is denied the right to vote. Furthermore, the autonomy harm may sometimes exceed the physical harm sustained by the victim, as is the case in many sexual harassment incidents. At other times, however, the victim’s physical harm or economic loss will outweigh the autonomy harm, as is often the case in automobile accidents. Even though autonomy violations are omnipresent, and the harm resulting from them can be severe, the law rarely recognizes a cause of action for violations of autonomy, nor does it provide redress for autonomy harms. The current legal approach to autonomy protection can best be characterized as anomalous and unprincipled. Therefore, from a normative perspective, it is untenable. In this article, we set out to make three novel theoretical and doctrinal contributions. First, we advance a comprehensive jurisprudential account of the relationship between rights and autonomy. Second, we show why existing law should be replaced with a legal regime that respects and protects individual autonomy in all cases. Finally, we develop a remedial framework designed to address autonomy violations. Mindful of administrability constraints, we incorporate three limitations to ensure that our proposal does not overwhelm the court system: (a) suits for autonomy violations would only be allowed when the plaintiff has a cause of action originating from the defendant’s infringement of her recognized legal right; (b) any such suit would undergo a strict de minimis scrutiny; and (c) no double recovery would be allowed in cases in which the plaintiff’s autonomy harm is subsumed in her physical or economic loss.